Analisis Video Musik Virtual Akun Komunitas @Indomusikgram di Media Sosial Instagram - Qilan Umara Ridwan (Fakultas Ilmu Komunikasi Universitas Pancasila, 2019)
This study aims to see how @indomusikgram uses Instagram for its music community that is analyzed by cyber community theory, using qualitative methods observed through document studies. The results showed that the community communicated as a forum for followers with a geographical, musical and Indonesian approach as a symbol of the presence of norms that tightened the community into an ally.